Transcription factor interactions at the PGK promoter in yeast - Packham, Elizabeth A. (1996)
Two new transcription factor binding sites have been identified within the phosphoglycerate kinase (PGK) gene promoter in the yeast Saccharomyces cerevisiae. The binding sites are upstream of the previously defined UAS, and are bound in vitro by the multifunctional transcription factors Reb1p and Cpf1p. A deletion of the Reb1p binding site was made from a PGK gene construct on a multicopy plasmid, and also targeted to the chromosomal copy of PGK. Deletions of the Rap1p and Abf1p binding sites in the UAS were also targeted to the chromosome. Analysis of RNA from the chromosomal deletion strains confirmed the central role of Rap1p in the activation of transcription from PGK. Reb1p and Abf1p were also found to be important for transcriptional activation. This is in contrast to results from experiments using multicopy plasmids carrying Reb1p or Abf1p binding site deletions from PGK. In this situation, neither the Reb1p site, nor the Abf1p site, plays a role in transcriptional activation.